International perspective on the basin-scale water-energy nexus - Metzger Terrazas, Luis (2016)
This chapter addresses the current state of water and energy resources management in different regions of the world using basin-scale case studies from North America, Latin America, and Africa. It focuses on the characterization of the current state and future projections of water and energy resources available in each basin as well as management of information gaps and potential links for integrating water and energy management. Agriculture demands large amounts of water in each basin and tends to be a priority when water distribution decisions are being made. Overall, this chapter provides a worldwide view of the state of water and energy in semiarid regions, showing cases of water management strategies that are being carried out in the case study basins considered in this chapter.